José Ruiz de Almeida Garrett: vida e obra - Pedro Miguel Videira Domingues (2022)
Introduction José Ruiz de Almeida Garrett was born in Paranhos, Porto, in the 10th of August, 1919. He excelled in the Pharmacology Investigation, teaching in the university, editing books and publishing several articles that were seen as na impulse for the development of the pharmacology knowledge. Methods Several visits to the Porto Medical College library archive, using as the main guide the book that was written in his homage, that the Professor Serafim Guimarães organized and edited meticulously. The Porto University main building's library archive and the interviews made to Walter Osswald (PhD), Serafim Guimarães (PhD) and Patrício Silva (PhD) were also a precious source of information to complete this work. Results From na exemplary student to a Cathedratic teacher and even Director of the Faculty of Medicine, Porto University, José Garrett never stopped to try and exceed his past glories or got satisfied with what he knew. In the middle of this journey, he was also the dad to eight kids, the responsible for several subjects in the Medical University and outsider of it, member of the Regional Council of Porto and the Regional Disciplinary Council of the Order of Physicians, member of the General Assembly, President of the Regional Council of Porto, director and writer of the newspaper "A Ordem", among others. Discussion A strong personality whose main influence was Alberto de Ataíde Malafaya Baptista (PhD), José Garrett left his mark in some of the most renowned names of the portuguese Pharmacology. To be highlighted are Walter Osswald (PhD), Serafim Guimarães (PhD) and Patrício Silva (PhD), the ones that felt his influence closely and due to it, grew and made other grow in a unique and immesurable way. Conclusion These words are no way enough to live up to what was the Teacher's spotless path, not only in the academic world but also in the scientific world. If some of the most importante homages (Silver and Gold European Merith medals) are not enough to describe what was a tough start path, with an unmatched resilience and effort, neither does this dissertation, an objective that was known, since day one, as impossible to achieve.